Introduction: the progress of elite ice hockey beyond the NHL - Carlsson, B.; Backman, J.; Stark, T. (Sport in Society: Cultures, Commerce, Media, Politics, 2020)
The last few decades have seen ice hockey blossom into a vibrant and multifaceted field of study in the humanities and social sciences. The result has been a veritable explosion of detailed and compelling accounts of various aspects of the game as a social phenomenon, including anything from the development of the National Hockey League (NHL) and the organization of women`s ice hockey to violence on and off the ice, as well as the staging of the sport as a Cold War battleground.However, one central aspect of ice hockey has remained largely ignored: the globalization of the game at large. Although numerous insightful deliberations on the formation of ice hockey as a cultural artifact have taken place in different parts of the world, there has been a dearth of wide-ranging considerations of how the sport has spread across the globe, as well as of what it has actually meant to the game in general, and to managers, players and fans in particular. This is perhaps especially true about ice hockey outside of North America, as the expansion of the European Union, the increasing internationalization of the NHL and the rise at the turn of the millennium 2000 of the transnational Russian equivalent, the Kontinental Hockey League (KHL), have contributed to a profound transformation of the sport both on and off the ice.Due to the call for abstracts, the issue has advantageously been stretched to include topics from China, Russia, Switzerland and the Czech Republic, as well as from the USA. The main focus still lies on the progress of domestic hockey leagues as well as on the cultural and psychological dominance of the NHL, with the KHL as a potential candidate, despite their mutual differences in explicit or implicit motives. Actually, the differences may form the breeding ground of their respective influence.